Determinants of Employee Performance in the Banking Sector: The Mediating Role of Creative Behavior and the Moderating Role of Reward - Mochammad Isa Anshori; Hosnaidah; Sri Puji Hartatik; Loso Judijanto; Novia Jamilati; Shinta Nuria Salsabila (Global Research Collaboration, 2026)
This study examines how learning orientation, knowledge sharing, employee motivation, and leadership reputation relate to employee performance, with creative behavior as an arbitrator and incentive as an intermediary. A correlational design that is quantitative was applied using PLS-SEM in SmartPLS 4. Questionnaire data were obtained from 100 purposively selected banking employees. The model was assessed through validity and reliability tests, R², path coefficients, mediation, and moderation analyses. Learning orientation, knowledge sharing, and leadership reputation were significantly associated with creative behavior, which was positively related to employee performance. Creative behavior mediated the links of learning orientation, knowledge sharing, and leadership reputation with employee performance. Employee motivation was not significantly associated with creative behavior, and reward had no significant direct relationship with employee performance. However, reward strengthened the association between creative behavior and performance of employes. The model demonstrated substantial explanatory power, explaining 72.4% of the variance in employee performance (R² = 0.724). Creative behavior therefore serves as a key pathway connecting individual and organizational factors with employee performance. Banks should promote learning, knowledge exchange, credible leadership, and reward practices that reinforce employee creativity.